Effective Detection of Real Trajectories of Highly Maneuverable UAVs Under Strong Noise Conditions - Kalinov, Ivan; Agishev, Ruslan (2018 Engineering and Telecommunication (EnT-MIPT), 2018)
In this paper, we present new an improved filtration method that is capable to detect the real trajectory of highly maneuverable UAV effectively. Highly maneuverable trajectories described here as fast turns of the object in sharp angles. The filtration algorithm was applied to multirotor UAV's tracking task. Coordinate measurements of the object, which trajectory includes high maneuvers, are used as input data. Measurement data was very noisy, and standard filtration methods (Kalman filter) didn't give satisfactory results. Our approach gave a better precision than known algorithms.